Critical Notes on Habeas Corpus in Peru - Cooper, H. H. A. (1970)
This paper offers an analysis of Habeas Corpus in the Peruvian legal system. For this purpose, three main issues are discussed. First, it tries to establish the nature of Habeas Corpus in Peru. The author points out that, although it is a legal institution whose origin is found in Constitutional Law, it has ended up being used in Civil and Criminal Law. Secondly, the legal nature of this institution is questioned; and in this case, the author tries to reveal whether it is an action or a remedy, properly speaking. Thirdly, the procedural regulation that this "guarantee" should follow within the national legal system is addressed.